Immunohistochemistry for FOSB and FOS is a Useful Ancillary Tool in the Diagnosis of Epithelioid Hemangioma but There are Pitfalls in Interpretation Including Expression in Other Vascular Lesions. (May 2023) - Tsui, Kwan Yee; Maclean, Fiona; Moir, Denis; Cheah, Alison; Bonar, Fiona; Tabot, Joel; Gill, Anthony J.; Vargas, A. Cristina
Introduction . Epithelioid hemangioma is a benign vascular neoplasm associated with FOS and/or FOSB protein overexpression detected by immunohistochemistry (IHC). Methods . The aim of our study was to determine the co-expression or independent IHC expression of FOS and FOSB in a cohort of epithelioid hemangiomas. We also included two cohorts of other vascular lesions: papillary endothelial hyperplasia and lobular capillary hemangioma / pyogenic granuloma. Results . We identified 50 cases of epithelioid hemangioma, 84% of which were cutaneous and the remaining involved other anatomic locations. Over two thirds of all cases expressed FOSB (68%; 34/50) while FOS immunoreactivity was identified in 46% of all cases. Co-expression of FOSB and FOS occurred in 37% of cases while 76% of all cases stained for at least one of the antibodies. Fifty-eight percent (n = 14/24) and 33% (8/24) of all cases of papillary endothelial hyperplasia expressed FOS and FOSB, respectively. Thirty-two per cent of lobular capillary hemangiomas (n = 8/25) were positive for either FOS or FOSB. Conclusion . In summary, we present the largest cohort of epithelioid hemangiomas assessed with both FOS and FOSB and demonstrated that the use of both antibodies increases the detection rate of these proliferations by 10%. Nonetheless, the use of thresholds may not be appropriate, as only a subset of lesional endothelial cells label with FOS/FOSB. Over half of all cases of papillary endothelial hyperplasia and a third of lobular capillary hemangiomas also displayed immunoreactivity with FOS and/or FOSB.